The Effectiveness of the Implementation of Supervisory Functions by the Head of Wassidik Division in Handling Corruption Cases at the West Sulawesi Regional Police - Andi Janganlolo; Askari Razak; Mursyid Mursyid; Hardianto Djanggih (Al-Ishlah: Jurnal Ilmiah Hukum, 2026)
This study examines the effectiveness of the implementation of supervisory functions by the Head of the Wassidik Division in handling corruption cases at the West Sulawesi Regional Police. Corruption in Indonesia has developed into a systemic and complex problem that requires professional, accountable, and transparent law enforcement. The investigation stage plays a crucial role in determining the success of uncovering corruption cases, making supervisory functions essential in ensuring procedural compliance and preventing abuse of authority. This research employs an empirical legal approach with a sociological perspective, focusing on law in action. Data were collected through interviews and document studies, then analyzed qualitatively using descriptive, interpretative, and evaluative techniques. The findings indicate that the supervisory function has been implemented but has not yet reached optimal effectiveness. Several inhibiting factors were identified, including limitations in human resources, inadequate infrastructure, weak inter-unit coordination, organizational cultural challenges, regulatory weaknesses, and the complexity of corruption cases. External intervention and limited budget allocation also affect supervisory performance. Strengthening institutional capacity, improving human resource competence, enhancing technological support, and reforming organizational culture are necessary to improve supervisory effectiveness. The study concludes that effective supervision is essential to ensure high-quality investigations and to support fair and accountable law enforcement in corruption cases